Suportes de simulação como objetos intermediários para incorporação da perspectiva da atividade na concepção de situações produtivas - Moura, Daniel Braatz Antunes de Almeida (2015)
Understanding the work in order to transform it is the concern of ergonomics. To expand its capacity of effective intervention this discipline gets closer to the field of engineering, especially the production engineering, searching for methods, techniques and tools, which assist it in the design process of productive facilities. The knowledge domains related to the engineering design and, specifically, the workspace design might be of a substantial contribution to the effectiveness of the incorporation of the activity’s perspective (according to the concept of situated ergonomics) in this process. From a theoretical and conceptual articulation, which laid the foundation to the field research in an oil refining company, is sought the comprehension of how the different simulation supports were determinant to the incorporation of rationale, interests, constraints and expectations from the actors participating in the conception process. To achieve this comprehension is used the concept of intermediary objects of conception and their theoretical stances in the axis “commissioning-mediator” and “closed-open”. The research makes evident the role the simulation supports play in the creation of simulation situations allowing divergent (and innovative) processes in the action of designing technical systems and convergent processes in the conduction of the project. The prescriptive propositions (from the practical world, including the activity’s perspective) and descriptive (from the theoretical world, containing in it the exact sciences and related technical questions) are also incorporated in the articulation, allowing a dialogic process of conception. The research presents recommendations which enable the design of productive facilities to entail an ongoing and distributed conception, having the simulation as an instrument oriented to the object (design action of the technical system), to the other (coordinated action) and to the self (when encompassing space to its development, learning and transformation).